Detection of Conjugate Points on Pair of Overlapping Image using Epipolar Correlation - Kamal Saluja, Kanika Khetarpal, (International Journal of Scientific Research and Management (IJSRM), 2015)
Automation of the entire image mapping system is the ultimate goal of current research efforts in imagemetrology. In this paper, author presents the design and implementation of a MATLAB program thatautomates the processes involved in locating conjugate points on a pair of overlapping photograph usingepipolar correlation. In order to achieve this, sets of overlapping photographic stereopairs from differentsources were collected and used as input. The program was designed to perform the following processes;load the photographic stereopair, carryout an automated feature extraction to extract interest points in bothphotos, match these points putatively and remove false matches (outliers). The resulting inlier points wereused to compute the fundamental matrix describing the epipolar geometry between the photographicstereopair.